Best Management Systems to Intensify Soybean Production - G. R. Balboa; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2018)
The aim of this study was to evaluate different management systems to close the yield gap in soybean production. A soybean experiment was established in Scandia, KS, evaluating five management systems under both rainfed and irrigated conditions. For the 2017 season, dryland and irrigated average yields were similar (63–65 bu/a) due to herbicide injury on the irrigated phase. In both water scenarios, intensification (high input) increased yields compared with common practice (low input) systems. Under irrigation, a consistent response to a balanced nutrition program was documented.
Keywords: best management systems; soybeans; yield